2017
DOI: 10.3390/nu9091042
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bioavailability of Omega-3 (DHA) through Alpha-Tocopheryl Phosphate Mixture (TPM) after Oral Administration in Rats

Abstract: Benefits of Omega-3 Docosahexaenoic acid (DHA) supplements are hindered by their poor solubility and bioavailability. This study investigated the bioavailability of various formulations of Omega-3 and tocopheryl phosphate mixture (TPM), following oral administration in rats, and assessed whether TPM could improve the oral absorption of DHA. The rats were administered with a high (265.7 mg/kg) or low dose (88.6 mg/kg) of DHA. TPM was examined at 1:0.1 w/w (low TPM dose) and 1:0.5 w/w (high TPM dose). Over 24 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…On the negative side, the acquisition of beneficial properties from omega 3 fatty acids is restricted due to poor water solubility and weak oral bioavailability. For example, fish oils are prone to lipid oxidative processes due to their high level of unsaturation, which can affect their regular consumption by promoting a fishy and rancid odor, and even promote adverse effects for health [126][127][128]. Notably, in fish oils, DHA and EPA are naturally bound by default in triacylglycerides, while a wide variety of fish oil capsules are composed of fatty acids bound in ethyl-esters and re-esterified triacylglycerides.…”
Section: Impact Of Bioavailabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…On the negative side, the acquisition of beneficial properties from omega 3 fatty acids is restricted due to poor water solubility and weak oral bioavailability. For example, fish oils are prone to lipid oxidative processes due to their high level of unsaturation, which can affect their regular consumption by promoting a fishy and rancid odor, and even promote adverse effects for health [126][127][128]. Notably, in fish oils, DHA and EPA are naturally bound by default in triacylglycerides, while a wide variety of fish oil capsules are composed of fatty acids bound in ethyl-esters and re-esterified triacylglycerides.…”
Section: Impact Of Bioavailabilitymentioning
confidence: 99%
“…Previous studies suggested that lipid-based formulations can improve the bioavailability of ω-3, as well as their ingestion with high-fat meals, which can improve their bioavailability [128]. It was also recommended that the ingestion of emulsified forms of omega-3 oils should have higher bioavailability patterns because such supplements can be enriched with absorption enhancers that advance the permeability for the epithelium cells [131].…”
Section: Impact Of Bioavailabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…At the intestinal epithelium, competition between the hydrophobic vitamins A, D, E, and K for selective uptake involving CD36 and SR-BI also modulates the efficiency of vitamin E uptake (38,39). Vitamin E can also influence the uptake of other lipids from the diet, as demonstrated with a mixture of αTP and di-tocopheryl phosphate able to increase the plasma levels of DHA by twofold (69).…”
Section: Modulation Of Signaling Pathways By Vitamin E Relevant For Imentioning
confidence: 99%